2019
DOI: 10.1371/journal.pbio.2006409
|View full text |Cite
|
Sign up to set email alerts
|

A single pair of leucokinin neurons are modulated by feeding state and regulate sleep–metabolism interactions

Abstract: Dysregulation of sleep and feeding has widespread health consequences. Despite extensive epidemiological evidence for interactions between sleep and metabolic function, little is known about the neural or molecular basis underlying the integration of these processes. D . melanogaster potently suppress sleep in response to starvation, and powerful genetic tools allow for mechanistic investigation of sleep–metabolism interactions. We have previously identified neuron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
132
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(145 citation statements)
references
References 92 publications
4
132
0
Order By: Relevance
“…Central nervous system neurons control sleep in a top-down fashion [85, 86], but bottom-up metabolic signals from glia [17, 24, 87, 88], muscle cells [32, 88-90] and adipocytes [91, 92] affect activity of sleep regulating neurons. While several gene products have been reported to regulate both metabolism and sleep [4, 9, 21-23, 25, 26, 32, 41, 89, 90, 93, 94], the mechanism of the metabolic regulation of sleep has heretofore remained opaque.…”
Section: Discussionmentioning
confidence: 99%
“…Central nervous system neurons control sleep in a top-down fashion [85, 86], but bottom-up metabolic signals from glia [17, 24, 87, 88], muscle cells [32, 88-90] and adipocytes [91, 92] affect activity of sleep regulating neurons. While several gene products have been reported to regulate both metabolism and sleep [4, 9, 21-23, 25, 26, 32, 41, 89, 90, 93, 94], the mechanism of the metabolic regulation of sleep has heretofore remained opaque.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have examined the interactions between sleep and feeding, these have typically compared fed and starved animals without examining the effects of specific dietary components on sleep regulation [11,36,66,67]. In Drosophila , feeding of a sugar only diet is sufficient for normal sleep duration [68], and evidence suggests that activation of sweet taste-receptors alone is sufficient to promote sleep [65,69].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors have been identified as essential regulators of starvation-induced sleep suppression. For example, we have found that flies mutant for the mRNA/DNA binding protein translin , the neuropeptide Leucokinin , and Astray, a regulator of serine biosynthesis, fail to suppress sleep when starved [38,66,67]. Further, activation of orexigenic Neuropeptide F -expressing neurons or the sweet-sensing Gr64f -expressing neurons suppress sleep, suggesting that activation of feeding circuits may directly inhibit sleep [69,77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of Lkr in IPCs results in altered dilp transcription in a diet‐specific manner, suggesting that leucokinin interacts with insulin signaling to control metabolism and stress response. In addition, starvation‐induced sleep in flies is also under the control of leucokinin neurons‐IPC connectivity (Yurgel et al, ). Finally, the neuropeptide Allatostatin A (AstA) positively regulates expression of dilp3 in IPCs (Hentze et al, ).…”
Section: Factors Regulating Ipcs and Dilp Productionmentioning
confidence: 99%